Baited remote underwater video stations as a potential tool for assessing coastal rocky fishes in Chile - Alejo J. Irigoyen; Andrés Flores; Santiago Gacitúa; Pablo Merlo; Rodrigo Wiff; T. Mariella Canales (Fisheries Management and Ecology, 2024)
Coastal rocky fish species support important fishing activities, but basic information is lacking for many before catches decline. Monitoring and management of coastal rocky fish species is urgently needed in Chile, but knowledge of these species is fragmentary at best. Performance of Baited Remote Underwater Video Stations (BRUVS) for assessing rocky fish assemblages was evaluated in south‐central Chile. Seven medium‐ to large‐sized exploited species dominated fish assemblages in the survey area, including five small cryptic rocky reef fishes, one agnathan and a catshark species. These seven species represented 78% of the species targeted by commercial fishing in the survey area. Furthermore, this tool provided new information on behaviour of rocky fish species. The simple, inexpensive and light nature of single‐camera BRUVS may be crucial for maintaining monitoring programs along remote areas of Chile.